The formation of health care thinking at early ages - A. Guchetl, Asiet (2019)
The article discusses the need for early childhood health education school ages, which is equivalent to providing health care for the individual in an educational system, such as health care, which allows individuals to create a value and motive for maintaining their health. It also has a form of life and health model.